Representasi Maskulin Jokowi Pada #JKWVLOG Tinju Dalam Analisis Semiotika Roland Barthes - Lymbarski Caesariano; Yulianti Fajar Wulandari; Murtiadi Murtiadi; Yan Bastian (Prisani Cendekia Institute, 2022)
The purpose of this research is to find out the symbols that appear on a video blog or vlog. In this study, a video blog or vlog becomes the object of research. Video blog (vlog) featuring boxing with the concept of imaging an adult male figure with a masculine appearance. President Joko Widodo or Jokowi is one of the vloggers. In the video blog (vlog) he made with the title of the blog entitled JKWVLOG